Nilai-nilai Kearifan Budaya Jawa Dan Peranannya Dalam Mewujudkan Masyarakat Madani : Perspektif Islam - Oktafia, Renny (STAI Miftahul Ula Nganjuk, 2017)
Abstract: Javanese is the most populous tribe in Indonesia. Javanese themselves have a culture that is still run by the Java community. In a culture that possessed the Java community, if there is disclosed a lot of wisdom values ââtherein. From the discovery of the values ââof this wisdom, if practiced, it can improve the condition of the nation today, especially those related to moral values ââbegin to shift in society today. And in the end with improving moral values ââof society, the civil society can realize the objectives of nation building. The purpose of this study is to raise the values ââof Javanese cultural wisdom in creating a civil society. By using qualitative research method refers to the study of literature. Based on this study, of the values ââof Javanese cultural wisdom is revealed there are moral values ââwhich are very useful in shaping civil society.